2020
DOI: 10.1177/0194599820937676
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Accuracy of Ultrasound for Sizing Salivary Ductal Calculi

Abstract: Objectives The present study was developed to evaluate the accuracy of in vivo ultrasound sizing for parotid and submandibular salivary gland calculi, as compared with ex vivo pathology sizing with a standard plastic ruler after extraction. Study Design Retrospective chart review. Setting Ultrasound is frequently used to size salivary calculi and make treatment decisions, but the accuracy of measurements from this modality has not been validated. Subjects and Methods We evaluated and reviewed the charts and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Besides, calculi within the distal duct are not shown accurately with US. Recently it was reported that ultrasound measurements of salivary stones in millimeters correlated highly with ex vivo measurements after removal ( 7 , 8 ). Conventional 2D radiography is still routinely used in daily practice nowadays.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, calculi within the distal duct are not shown accurately with US. Recently it was reported that ultrasound measurements of salivary stones in millimeters correlated highly with ex vivo measurements after removal ( 7 , 8 ). Conventional 2D radiography is still routinely used in daily practice nowadays.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which DD is obviously difficult, ultrasound-guided diagnostic techniques [41,103] and the simultaneous application of US and sialendoscopy added diagnostic value, the latter by providing a singular, real-time, three-dimensional intra-and extraductal overview [103]. Besides this, US provides diagnostic information in the preparation [103,137], as support in the treatment [103,[138][139][140][141][142][143][144][145] and in the (post-therapeutic) follow-up [69,79,146] in sialolithiasis.…”
Section: Obstructive Sialadenitis Caused By Sialolithiasismentioning
confidence: 99%